Spectrum of Neurological Manifestations of COVID-19 in Children: A Hospital-Based Study in Uttar Pradesh, India - Pallavi Gupta (International Journal of Human and Health Sciences (IJHHS), 2026)
COVID-19 infection and its neurological manifestations were seen in children. A retrospective study was performed on hospitalized paediatric patients aged between 1 month and 18 years with confirmed SARS-CoV-2 to determine the frequency of different types of neurologic findings of hospitalized children with COVID-19. This study was conducted at Saraswathi Institute of Medical Sciences in Uttar Pradesh, India. Neurological manifestations were defined as the presence of any of the following symptoms: seizure, altered mental status, behavioral/personality change, ataxia, stroke, muscle weakness, smell and taste dysfunctions, and focal neurological disorders. A total of 250 children with COVID-19 were admitted and their mean age was 6.94±4.06 years. 53.6% of the patients were male. The most frequent neurological manifestation was seizure (26%), followed by muscle weakness (10%), loss of consciousness (24%), and focal neurological disorders (24%). Other neurological manifestations included headache (n=40), movement disorders (n=25), behavioural or personality change (n=12), ataxia (n=10), and stroke (n=10). 16% of the patients had leukocytosis. A neutrophil count above 70% was seen in 20% of the patients. 80% had a positive reverse-transcription polymerase chain reaction (RT-PCR) test for SARS-CoV-2. During the pandemic outbreak, hospitalized children with COVID-19 should be evaluated for neurological signs because it is common among them and should not be under-estimated. International Journal of Human and Health Sciences Vol. 10 No. 04 Oct’26 Page: 240-245